CONCEPTUAL FOUNDATIONS MANAGEMENT OF SOCIAL AND ECONOMIC EFFICIENCY SUBSYSTEMS OF HEALTHCARE - Парфёнова, И. И. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2012)
A concept of management in improving the socio-economic efficiency of health subsystems macro-, meso-, micro-and miniurovney. Its content is common to all levels of management aspects and informational aspects of performance monitoring.